Chemoselective Peptide Backbone Diversification and Bioorthogonal Ligation by Ruthenium‐Catalyzed C−H Activation/Annulation. Issue 13 (7th May 2021) - Song, Liangliang; Ojeda‐Carralero, Gerardo M.; Parmar, Divyaakshar; González‐Martínez, David A.; Van Meervelt, Luc; Van der Eycken, Johan; Goeman, Jan; Rivera, Daniel G.; Van der Eycken, Erik V.
Abstract: The field of peptide derivatization by metal‐catalyzed C−H activation has been mostly directed to modify the side chains, but poor attention has been given to the peptide backbone. Here we report a ruthenium‐catalyzed C−H activation/annulation process that can chemoselectively modify the peptide backbone producing functionalized isoquinolone scaffolds with high regioselectivity in a rapid and step‐economical manner. This strategy is characterized by racemization‐free conditions and the production of fluorescent peptides, and peptide conjugates to drugs, natural products and other peptide fragments, providing a chemical approach for the construction of novel peptide‐pharmacophore conjugates. Mechanistic studies suggest that amide bonds of peptide backbone act as the bidentate directing group to promote the C−H activation/annulation process. This report provides an unprecedented example of peptide backbone diversification and bioorthogonal ligation exploiting the power of ruthenium‐catalyzed C−H activation. Abstract :